Buddhist Teachings in Peacebuilding: A Study of Moral Guidance on Social Justice and Solidarity - Foysal, Foysal (The Jahangirnagar Review Part-C, 2026)
In today’s world some of the issues like a crusade, religious violence, and religious ignominy are some of the most widely discussed. The enumeration of negative terms associated with religion, such as violence and aggressiveness, is considerable. Many times, Buddhism is not exempt from this charge. Where Buddhism has identified itself as a religion of non-violence, the question is, when there is conflict and violence in society by people known as Buddhists, is it justified by this religion? On the other hand, what kind of guidance is available in Buddhism to establish peace and equality in society and prevent conflict? This study examines the moral position of Buddhism in dealing with extremism or conflicting behavior or anti-solidarity attitude. And the role of Buddhism in establishing peace has been reviewed. The purpose of this research work is to identify the inconsistencies of Buddhist moral discipline with the behaviors practiced by the followers in creating conflict, To, identify the prevailing misconceptions about conflict and solidarity in this religion, and at the same time to review how it is effective in establishing peace in the society by presenting specific religious and ethical discipline of Buddhism on conflict and solidarity. In this context, here I analyze the Buddhist moral perspective by reviewing and studying Buddhist texts, books, scholarly articles, and other relevant information in four particular focuses, (i) justice, ii) racial discrimination, iii) economic inequality, and iv) misuse of power. At the same time, the relevance of Buddhist teachings in all these areas for establishing social peace and solidarity has been highlighted